Mobile Technology for Learning Assessment: Design Process for the NursE-Quiz Mobile Application - Lajane, Halima; Gouifrane, Rachid; Arai, Mounir; Qaisar, Rabia; Chemsi, Ghizlane; Radid, Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This paper traces the development of a mobile application designed to simplify and support learning in nursing education. This application is based on the principles of dynamic formative evaluation, a method that encourages student involvement in the formative assessment process and supports student learning through formative feedback. A formative assessment model was derived from these principles and informed the application’s design. This mobile application project, which ran from February to September 2020, aimed to contribute to the improvement of formative assessment practices through the development of a learner-centered assessment tool and the identification of key formative processes within the application. The application’s functionality was based on the needs of the actors, which were analyzed according to Black and William’s theoretical perspectives on formative assessment and Keller’s motivational model; both were used to inform the pedagogical design of the application. This application is intended for nursing teachers working in ISPITS in Morocco and student nurses enrolled in the professional license cycle in these training institutes